TWO FRAGMENTS OF A BOWL WITH THE IMAGE OF FEATHERS OF THE KHOREZMSHAKH PERIOD FROM THE SETTLEMENT OF MIZDAKHKAN (American Journal of Research in Humanities and Social Sciences, 2023)
The article deals with the issues related to the image of watering bowls with a zoomorphic motive, an autopsy of the last year's archaeological season from the "Southern Settlement" in the ancient settlement of Mizdahkan. Their morphological, ornamental features are analyzed and plot motives are interpreted. The area of distribution of such a product is given and compared with analogues in close and distant regions